The Influence of Socialization Activities on the Understanding of Tolerance of Mosque Youth in Gedangan Village, Sidayu District, Gresik Regency - Syailendra Pratama Wicakson; Marsanda Duwi Ica Sari; Anindya Destyn W; Moch. Rizki Eko W; Salsabila RK Syaharani (PT. TAKAZA INNOVATIX LABS, 2026)
Tolerance is a value upheld in various religions, which is manifested as an open attitude to respect and accept differences. However, the phenomenon of disagreement and lack of understanding of differences still often occurs among young people. This study aims to explain how tolerance socialization is implemented for mosque youth in Gedangan Village, Sidayu District, and to assess the extent to which their understanding improves after being involved in the activity. This study uses a quantitative approach with a one-group pretest-posttest design involving 23 respondents. Data collection was carried out using a questionnaire and analyzed using the Shapiro-Wilk normality test and the Paired Samples T-Test. The results of the normality test showed that the data were normally distributed (Sig. pre-test = 0.416; Sig. post-test = 0.055). Furthermore, the results of the Paired Samples T-Test showed a significant difference with a calculated t value of -4.354 and a Sig. (2-tailed) value of 0.000 < 0.05. It can be concluded that the socialization activities had a significant influence on increasing the understanding of tolerance among mosque youth in Gedangan Village.